Encyclopedia of urban studies - Hutchison, Ray; Gale Group (Thousand Oaks, Calif. SAGE Publications, 2010)
Covers all aspects of cities, their suburbs, and other urban areas. Includes urban economics, urban planning, urban architecture, urban ecology, urban transportation systems, urban politics, and urban social relations.
v. 1. A - M -- v. 2. N - Z.
Electronic reproduction.
Keywords: Cities and towns -- Encyclopedias; Sociology, Urban -- Encyclopedias; Electronic books